Can a semiochemical deter cats from trash cans?. Issue 1 (January 2023) - Menuge, Fanny; Pageat, Patrick; Arroub, Sana; Teruel, Eva; Marcet-Rius, Míriam; Monneret, Philippe; Cozzi, Alessandro
Objectives: The interaction between free-roaming cats and humans can lead to cohabitation issues. One such issue is the nuisance caused when cats scavenge and scatter garbage, particularly in cities. This study aimed to investigate the impact of a semiochemical on cat avoidance behaviour. Methods: Five cats were included in the study, in a crossover design. A 10 min choice test involving two garbage cans, one sprayed with the semiochemical and the other sprayed with a control solution, was performed in a controlled setting. The parameters observed were exploration, proximity, latency to approach and first choice. Results: Cats spent less time exploring (general linear mixed model [GLMM]; degrees of freedom [DF] = 1; F = 14.23; P  <0.0001) and in proximity to the treated garbage can (GLMM; DF = 1; F = 13.25; P  <0.0001). Additionally, although there was no significant difference in the first choice ( P  = 0.5300), the latency to approach tended to be longer for the treated garbage can (frailty model; DF = 1; χ 2  = 3.49; P  = 0.0610). Conclusions and relevance: The present study demonstrated that this semiochemical can deter cats from trash cans in a controlled setting. Further studies are needed to explore the efficiency of the semiochemical deterrent in a real-world setting to improve human–cat cohabitation.